Management control systems - Anthony, Robert N.; Dearden, John; Robert N.Anthony (Homewood, Ill. : R.D. Irwin, 1980)
This fourth edition of the book follows closely the format of the third. All of the text, however, has been rewritten to incorporate new findings from the literature and observations from practice. The book focuses on newer topics such as the control of discretionary costs, profit centers, and the programming process.
Includes bibliographical references and index.
hza 27/09/2018
Loans
Keywords: Industrial management; Cost control